Tooth wear in relation to physical salivary characteristics among gastroesophageal reflux disease - Abdulrazak, Marwa S; Qasim, Alhan A; Falih, Ali I (Journal of Baghdad College of Dentistry, 2023)
Background: Gastroesophageal reflux disease, is a quite prevalent gastrointestinal disease, among which gastric content (excluding the air) returns into the oral cavity. Many 0ral manifestations related t0 this disease include tooth wear, dental caries also changes in salivary flow rate and pH. This study was conducted among gastroesophageal reflux disease patients in order to assess tooth wear in relation to salivary flow rate and pH among these patients and the effect of gastroesophageal reflux disease duration on this relation. Materials and methods: One hundred patients participate in this cross-sectional study for both genders and having an age range of 20-40 years old, patients had been endoscopically identified as having gastroesophageal reflux disease using the classification of Los Angeles (LA), who were attending the Gastroenterology and Hepatology Teaching Hospital in Baghdad. and divided into two groups: group A with grade severity mucosal breakage not longer than 5 mm and Group B with grade severity mucosal breakage more than 5 mm long, Smith and Knight (1984) tooth wear index criteria were used for the assessment of tooth wear. For measurement of salivary flow rate and pH, saliva sample (unstimulated) had been collected. Results: Of the entire sample (90%) were having tooth wear. Tooth wear was higher in grade B severity than in grade A severity among patients with gastroesophageal reflux disease duration of two years or less, while it was higher in grade A than in grade B among patients with a duration of more than two years but all these results were statistically non-significant. Salivary flow rate and pH showed a non-significant reduction with increasing gastroesophageal reflux disease severity for both of groups concerning disease duration. The correlation of total tooth wear with salivary flow rate and pH was a significantly weak negative correlation in grade A, while a nonsignificant weak negative correlation in grade B. Conclusions: The findings of the present study concluded that patients with gastroesophageal reflux disease recorded a high occurrence of tooth wear and there was a negative correlation of tooth wear with salivary flow rate and pH among patients with gastroesophageal reflux disease.